Cytotoxicity of Two Resin-Based Sealers and a Fluoride Varnish on Human Gingival Fibroblasts - Forghani, Farshid Reza; Parirokh, Masoud; Paseban, Hamzeh; Asgary, Saeed; Askarifard, Sara; Esmaeeli Mahani, Saeed (Iranian Endodontic Journal, 2015)
Introduction: Assessment of cellular cytotoxicity is a regular method for evaluating the biocompatibility of novel materials. In a recent study, 5% fluoride varnish (Duraflur) has shown reasonable sealing ability and coverage of root canal walls when used as a sealer. The aim of the present study was to compare cytotoxicity of Duraflur varnish with two popular commonly used root canal sealers (AH-Plus and AH-26) on human gingival fibroblasts (HGF). Methods and Materials: The HGFs were incubated with different concentrations (1/2, 1/4, and 1/8) of AH-plus, AH-26, and Duraflur varnish for 24 h. The percentage of cell viability was assessed with methyl-thiazol-tetrazolium (MTT) assay. The data was analyzed using the one-way ANOVA followed by Student-Newman-Keuls test. The level of significance was set at 0.001. Results: MTT assay showed that higher concentrations of the tested materials resulted in lower viability of HGFs. AH-Plus showed significantly greater cell viability compared to AH-26 at all dilutions (P<0.001); however, no significant difference was found between Duraflur and AH-Plus in terms of cell viability at 1/8 dilution (P>0.001). Duraflur showed significantly higher cell viability compared to AH-26 except at 1/2 dilution (P<0.001). Conclusion: Although Duraflur varnish had better biocompatibility compared to AH-26, it should still be evaluated with further biocompatibility tests such as intraosseous and subcutaneous implantation.